Safety and immunogenicity of unadjuvanted subvirion monovalent inactivated influenza H3N2 variant (H3N2v) vaccine in children and adolescents. Issue 36 (23rd August 2019) - Munoz, Flor M.; Anderson, Evan J.; Bernstein, David I.; Harrison, Christopher J.; Pahud, Barbara; Anderson, Edwin; Creech, C. Buddy; Berry, Andrea A.; Kotloff, Karen L.; Walter, Emmanuel B.; Atmar, Robert L.; Bellamy, Abbie R.; et al.
Abstract: Objective: In response to the emergence of influenza viruses with pandemic potential, we evaluated a swine-origin influenza A/H3N2 variant (H3N2v) vaccine in children. Study design: This multicenter phase II open-label study assessed the safety and immunogenicity of two doses, 21 days apart, of investigational unadjuvanted subvirion monovalent inactivated H3N2v vaccine administered via intramuscular injection. Children 6–35 months of age received 7.5mcg or 15mcg of hemagglutinin (HA)/dose; children 3–17 years of age received 15mcg HA/dose. Safety and reactogenicity were assessed by measuring the occurrence of solicited injection site and systemic reactions in the 7 days after each vaccination; adverse events were assessed for 42 days and serious adverse events for 7 months after the first vaccination. Immunogenicity was evaluated by measuring hemagglutination inhibition (HAI) and neutralizing (Neut) antibodies to H3N2v prior to and 21 days after each vaccination. Cross-reactivity against seasonal H3N2 strains was evaluated. Results: The H3N2v vaccine was well tolerated. Transient mild to moderate injection site tenderness, pain and erythema was observed, with the most commonly reported systemic reactogenicity being irritability in children 6–35 months, and headache and fatigue in children 9–17 years old. Children 6–35 months old, whether they received 7.5mcg or 15mcg/dose, had low HAI and Neut antibody responses after two doses compared to older children. Children under 9 years of age required two doses of vaccine to demonstrate a response, while 9–17 year olds responded well after one dose. Previous influenza vaccination and older age were associated with higher immune responses to H3N2v vaccine. Children 9–17 years of age also developed cross-reactive antibodies against recent seasonal H3N2 influenza viruses. Conclusion: The H3N2v vaccine was safe and immunogenic in children and adolescents. Age-related increases in immunogenicity against H3N2v and seasonal H3N2 viruses were observed, suggesting prior priming via infection and/or immunization. Clinical trial registry: The trial is registered with clinicaltrial.gov: NCT02100436 .